2011
DOI: 10.1007/s11033-011-1232-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of MAP2K9 and MAPK6 during pathogenesis of Alternaria blight in Arabidopsis thaliana ecotype Columbia

Abstract: Arabidopsis thaliana ecotype Columbia was used as a host in order to investigate the involvement of MAP kinase machinery in the pathogenesis of Alternaria blight. Semi-quantitative reverse transcriptase polymerase chain reaction and quantitative real time PCR based approaches were used to determine the change in transcript profile of MAP2K9 and MAPK6 in leaves of A. thaliana ecotpe Columbia at early, middle and late stages of Alternaria blight infection. It was observed that the expression of both MAP2K9 and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…For instance, two mitogen activated protein kinases (MAPK) that encode MAPK3 in A. thaliana were transcriptionally up-regulated (contig2100 and contig2102). Similarly, a member of the MAP Kinase Kinase family (MKK9, contig14909) and a protein kinase kinase kinase (MAPKKK14, contig7892) that play a role in leaf senescence during pathogenesis by Alternaria blight in A. thaliana were also transcriptionally up-regulated [ 28 ]. The activation of MAPK through wounding is dependent on the direct binding of calmodulins (CaM) in a Ca 2+ dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, two mitogen activated protein kinases (MAPK) that encode MAPK3 in A. thaliana were transcriptionally up-regulated (contig2100 and contig2102). Similarly, a member of the MAP Kinase Kinase family (MKK9, contig14909) and a protein kinase kinase kinase (MAPKKK14, contig7892) that play a role in leaf senescence during pathogenesis by Alternaria blight in A. thaliana were also transcriptionally up-regulated [ 28 ]. The activation of MAPK through wounding is dependent on the direct binding of calmodulins (CaM) in a Ca 2+ dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, our results indicate the fine tuning of the JA pathway in cotton in response to the infestation by aphids and whiteflies. Further, in addition to changes in the expression of the genes involved in JA and ET biosynthesis, we also identified that the expression of hormonal signaling kinases, including MAP2K9 and MAPK6, was also altered, and the relation of MAP kinases in defense mechanisms involving JA, SA, and ET is well established [63]. We also identified that the expression of enzymes involved in oxidative radical scavenging were suppressed after the infestation by aphid and whiteflies (Table 4); these may lead to an increase in oxidative radicals and H 2 O 2 in the phloem sap, which is a probable strategy that is deployed by cotton plants against insect infestation [38].…”
Section: Discussionmentioning
confidence: 99%
“…In Brassica crops, Alternaria brassicae incites Alternaria blight disease against which little information is available on the defense pathways. Fortunately Arabidopsis thaliana has been demonstrated as host for Alternaria brassicae (6), and the genes of MAPK signaling cascade in Arabidopsis thaliana are evolutionary conserved [6,7]. Therefore, in the present study, MAPK signaling cascade responsible for biosynthesis of camalexin in Brassica rapa has been elucidated using the genomic information from Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%